Remembering David Montgomery (1926-2011) and His Impact on Working-Class History - Barrett, James R. (Labour / Le Travail, 2012)
A eulogy is presented for the labour historian of the U.S. working class David Montgomery.
Keywords: EULOGIES; HISTORIANS – United States; MONTGOMERY; David